"Something to be Desired": The Reproduction of Queer Ways of Life (PROKLA. Journal of Critical Social Science, 2019)
This paper asks how queer ways of life can be understood as producing and reproducing themselves today. It suggests that, for many, living a queer life in a desirable way has long entailed having to escape, at least to some degree, from one of the primary sites of social reproduction – namely, the family – along with the construction of alternative networks of care and support, often facilitated through (counter-cultural and other) spaces beyond the domestic realm. I argue that there is a perhaps surprising degree to which the ways that this takes place is evident in (fairly mainstream) cultural representations of queer social life in film and television from the last 30 years; surprising given that, as others have rightly noted, this in some ways contradicts many other equally prominent recent representations of LGBT assimilation within dominant institutions, and particularly marriage and the family, amidst the emergence of a thoroughly de-politicised “new normal”.
Keywords: Queer Ways of Life; Family; Homonormativity; Heteronormativity